Konsep pengembangan lanskap wisata alam di Desa Wisata Singakerta, Kabupaten Gianyar - I Gusti Agung Ayu Rai Asmiwyati; Ari Dwijayanti; I Gusti Alit Gunadi (Jurnal Arsitektur Lansekap, 2025)
The natural resource potential in Singakerta Village can be a tourist attraction necessary for the development. The location of this village is very strategic and is a chance buffer for Ubud tourists. Natural resources such as agroculture and river can be developed as a natural tourist attraction. The problem found is that the potential of the village has not been maximally developed, so it is necessary to create a development concept that is suitable for natural tourism spaces. The research purposed to make a landscape development concept for nature attraction with the results of the analysis and synthesis of tourism space development. The research method is qualitative and the research stage is from inventory, analysis, synthesis, and concept. The result is nature tourist attractions which are Subak Batuh and Wos River. A base concept that matches on functional and research purpose of village tourists from realizing nature approach is Tri Hita Karana philosophy, while the space concept is divided into three such welcome space, rice field tourism space, river tourism space, religious tourism space, and tourism support space. Circulation concepts is network circulation, and the vegetation concept is shade vegetation, buffer vegetation and aesthetic vegetation. This landscape development concept be input for the village and minus out-of-bounds research will follow by the next researcher.